Political and Economic Activities of the PRC on the Balkan Peninsula Romania: A Case Study - Ciborek, Przemysław (New Dynamics in Asia, 2020)
The recent growing political and economic presence of the People’s Republic of China on the Balkan Peninsula draws more and more attention from the European Union, the United States, and Japan, as well as Russia and Turkey. The institutionalized expression of Chinese interest in the Central and Eastern Europe region is the 16+1 format launched in Warsaw in 2012 by the then Chinese Prime Minister, Wen Jiabao, which, by definition, should be a multilateral platform for cooperation between the countries of Central and Eastern Europe and China. The current bilateral relations between China and Romania are based on the declaration of an enhanced agreement concluded in 2013. In the context of economic cooperation with China, the identification of key sectors and investment projects of Chinese interest remains the most critical task for Romanian diplomacy. In the case of Romania, the most advanced negotiation projects undertaken by Chinese entities include, among others: possible introduction of Huawei’s 5G technology and the Cernavoda Nuclear Power Plant. Through quantitative and qualitative analysis, this study analyses Chinese investment in Romania as well as its limitations. The primary aim of this research is to identify Chinese motivations regarding investments in Romania, as well as their efficiency and impact on the domestic economy. In this context, the growing importance of Sino-American interactions in the region – including Romania – reflects the global tensions in relations between Washington and Beijing.